Penatalaksanaan Fisioterapi Pada Kasus Penyakit Paru Obstruksi Kronis Dengan Komplikasi Pneumotoraks - Salsabila, Shofa Salma, - (2021)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a lung disease that causes sufferers to have difficulty breathing and over time can cause damage to lung tissue. The damage to the lung tissue causes air to leak in the lungs so that air enters the pleural cavity and causes pneumothorax. Objective: To determine the effect of physiotherapy management in cases of chronic obstructive pulmonary disease with pneumothorax complications. Methods: Literature review, using physiotherapy interventions in the form of diaphragm breathing exercises, pursed lips breathing, deep breathing, chest expansion, nebulizers, cough exercises, postural drainage, percussion and vibration, cardiorespiratory endurance training, infra red and modified breathing exercises by blowing a balloon. Results: Based on a study of 5 journals, the results of research in each journal can reduce the degree of shortness of breath, increase lung capacity, increase thoracic expansion, reduce secretion buildup, reduce spasm in the respiratory aids muscles and increase heart and lung endurance. Conclusion: Physiotherapy management has a positive effect and impact for patients with chronic obstructive pulmonary disease complicating pneumothorax.